Derivation of Human Skin Fibroblast Lines for Feeder Cells of Human Embryonic Stem Cells. (13th February 2018) - Unger, Christian; Felldin, Ulrika; Rodin, Sergey; Nordenskjöld, Agneta; Dilber, Sirac; Hovatta, Outi
Abstract: After the first derivations of human embryonic stem cell (hESC) lines on fetal mouse feeder cell layers, the idea of using human cells instead of mouse cells as feeder cells soon arose. Mouse cells bear a risk of microbial contamination, and nonhuman immunogenic proteins are absorbed from the feeders to hESCs. Human skin fibroblasts can be effectively used as feeder cells for hESCs. The same primary cell line, which can be safely used for up to 15 passages after stock preparations, can be expanded and used for large numbers of hESC derivations and cultures. These cells are relatively easy to handle and maintain. No animal facilities or animal work is needed. Here, we describe the derivation, culture, and cryopreservation procedures for research‐grade human skin fibroblast lines. We also describe how to make feeder layers for hESCs using these fibroblasts. © 2016 by John Wiley & Sons, Inc.